Auditory poverty and its discontents an essay - Dragičević, Nina (Errant Bodies Press, 2024)
Where sounding is understood as an exhibition of activity, vitality, and power, Nina Dragi?evi? proposes that we analyse sonic phenomena in econo-political terms.00In this essay?or is it perhaps a long love poem??she dives into the sounding-listening dynamics and reveals them as class relations in which audibility is not an event following an occurrence of sound but a point in an intersectional class structure. With audibility, or rather the lack thereof, comes auditory poverty. And where there is poverty, there is discontent. And where there is discontent, there is potential for an uprising.00Nina Dragi?evi? (born 1984) is a Slovenian poet, a writer, a sound artist and a sociologist. She is the author of the books Kdo ima druge skrbi (2014; Who has Other Worries), Slavne neznane: Zvo?ne umetnice v konstrukciji dru?be (2016; Famous Unknowns: Women sound artists in construction of society), Med njima je glasba: Glasba v konstrukciji lezbi?ne scene (2017; The Music Between Them: Music in construction of lesbian communities), Ljubav re?e greva (2019; Lover Says Let's Go), To telo, pokon?no (2021; This Body, Standing), Kako zveni oblast? (2022; Sound of Power), and Ampak, kdo? (2023; But Who?), and numerous electroacoustic compositions and sound installations